The Effect of Holistic Marketing on Brilliant Performance: An analytical research in the General Company for Food Products/The Headquarters - Hashim Fadhil, Zahraa; Khudair Abbas Al Doori, Yasmin (Journal of Economics and Administrative Sciences, 2024)
The current study investigated the role of holistic marketing in ambidextrous performance through conducting an analytical study. The study aimed at identifying the reality of the application of holistic marketing, its dimensions, and the ambidextrous performance and its dimensions in the General Company for Food Products, affiliated with the Ministry of Industry and Minerals. The research problem was diagnosed by the scarcity of studies that combine the two research variables, especially in the Iraqi industrial sector, as far as the researcher knows. Most of these research studies focused on one variable individually due to the novelty of the field of knowledge related to holistic marketing and ambidextrous performance, which constituted a knowledge gap worthy of research and investigation. This research relied on the questionnaire as the main tool for collecting data, as the questionnaires were distributed to (186) persons at various administrative levels (senior, middle, and executive). One of the most important results of the research is that there is a direct and positive effect of holistic marketing on ambidextrous performance. Paper type: Analytical research.